Older adults with lower working memory capacity benefit from transcranial direct current stimulation when combined with working memory training: A preliminary study - Assecondi, Sara; Hu, Rong; Kroeker, Jacob; Eskes, Gail; Shapiro, Kim (Frontiers in Aging Neuroscience, 2022)
Ageing is a very diverse process: successful agers retain most cognitive functioning, while others experience mild to severe cognitive decline. This decline may eventually negatively impact one’s everyday activities. Therefore, scientists must develop approaches to counteract or, at least, slow down the negative change in cognitive performance of ageing individuals. Combining cognitive training and transcranial direct current stimulation (tDCS) is a promising approach that capitalizes on the plasticity of brain networks. However, the efficacy of combined methods depends on individual characteristics, such as the cognitive and emotional state of the individual entering the training program. In this report, we explored the effectiveness of working memory training, combined with tDCS to the right dorsolateral prefrontal cortex (DLPFC), to manipulate working memory performance in older individuals. We hypothesized that individuals with lower working memory capacity would benefit the most from the combined regimen. Thirty older adults took part in a five-day combined regimen. Before and after the training, we evaluated participants’ working memory performance with five working memory tasks. We found that individual characteristics influenced the outcome of combined cognitive training and tDCS regimens, with the intervention selectively benefiting old-old adults with lower working memory capacity. Future work should consider developing individualized treatments by considering individual differences in cognitive profiles.